Transformed or Transferred? How Workers Perceive Managerial Control over Home Telework. Some Insights from an Italian Case - Iannuzzi, Francesco Eugenio; Campolongo, Francesco (Relations industrielles / Industrial Relations, 2023)
AbstractWe examined how home-based teleworkers perceived managerial control in an Italian context in order to gain insight into some of the organizational changes brought on by the COVID-19 pandemic. Drawing on studies of changes to managerial control over the past few decades, we show how workers have experienced the reconfiguration and hybridization of control practices and methods in home telework. Our results cast doubt on the widely held belief that telework is revolutionizing managerial control and work procedures. Organizational and power dynamics at work are key to determining how telework affects employee experiences.SummaryWe investigated the impact of the COVID-19 pandemic on labour relations, specifically by examining how teleworkers perceived control within various occupations in an Italian context. Telework has long been touted as having the power to displace traditional managerial control structures in favour of less hierarchical forms of supervision. However, scholars are still divided over whether it promotes greater employee autonomy or, on the contrary, results in greater managerial control. Research has frequently been influenced by specific circumstances. In earlier decades, the low prevalence of telework encouraged neither thorough research nor the ability to compare various organizational structures. Additionally, there has been a long-standing tendency to treat teleworkers as a homogeneous group, with little regard for within-group differences. Disparities among workers and among organizations can lead to inconsistent results.Our study was conducted mainly during the first waves of the pandemic in Italy, with a view to understanding if, how, to what extent and on what basis telework modifies managerial control processes and systems. We looked at how workers experienced managerial control in various occupations that differ in organizational form and managerial culture.In line with Storey’s (1985) concept of “layers of control” and, more generally, with studies on transformations of managerial control in labour processes, we argue that the emergency restructuring due to home telework caused a transfer of organizational conditions, these being a combination of existing methods, standards and forms of control. Our findings show how employees dealt with the hybridization, overlapping and differentiation of various forms of control during a time of widespread telework. In this way, we cast doubt on the simplistic association between telework and reduction of control, as well as on the potential of telework to bring fundamental change to organizational processes.